Survival advantage of upfront cytoreductive nephrectomy in patients with primary metastatic renal cell carcinoma compared with systemic and palliative treatments in a real-world setting. (1st November 2020) - Ljungberg, Börje; Sundqvist, Pernilla; Lindblad, Per; Kjellman, Anders; Thorstenson, Andreas; Hellström, Mikael; Kröger Dahlin, Britt-Inger; Thomasson, Marcus; Harmenberg, Ulrika; Lundstam, Sven
Abstract: Background: Recently, the CARMENA and SURTIME studies, suggested that upfront cytoreductive nephrectomy (CN) should be abandoned for patients with intermediate and high-risk metastatic renal cell carcinoma (mRCC). However, CN remains an indication in low-risk and when immediate systemic treatment is not required. The aim was to evaluate the long-term overall survival (OS) in patients with primary mRCC, based on the first line treatment. Methods: There were 1483 patients with primary mRCC in the National Kidney Cancer Registry from 2005 to 2013. Data on primary treatment, TNM stage, RCC type, tumor size, patient age and sex were extracted. Survival time was calculated from time of diagnosis to time of death or until July 2019. Mann-Whitney U and Chi-square tests, the Kaplan-Meyer method and Cox regression analyses were used. Results: Patients primary treated with CN had a significantly longer OS ( p  < .001) than patients primary treated with systemic therapy or palliation. In a Cox regression multivariate analysis, the hazard ratio for CN compared with no CN was 1.600, 95%Ci (1.492 − 1.691), p  < .001. Also occurrence of lymph node metastases, T-stage, patients age and year of diagnosis, remained as independent predictors of OS. Conclusion: Patients primary treated with CN survived significantly longer than patients primary treated with systemic therapy or palliation, in all age groups. CN was an important first-line treatment option in mRCC patients.